Occupational Health and Safety Risk Analysis Using Hazard Identification, Risk Assessment, and Risk Control Method at Final Waste Disposal Site Suwung, Bali - Ida Bagus Made Baskara Andika; Muhammad Zuvisco Sauqi; Ida Ayu Rai Widhiawati (Tecno Scientifica Publishing, 2026)
The Suwung Final Waste Processing Site, the largest landfill in Bali, faced major challenges, including overcapacity of waste piles, high fire risks due to methane gas accumulation, and the lack of a structured Occupational Health and Safety (OHS) system. These conditions posed significant hazards that directly affected the safety and health of workers. This study aimed to identify hazards, assess risk levels, and recommend appropriate risk control measures for operational activities at TPA Suwung. This research was conducted at TPA Suwung from March to April 2025, involving 18 workers as respondents. The study focused on four key operational activities: waste truck mobilization, waste reception, landfill structuring, and heavy equipment maintenance. The analysis was carried out using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method to systematically evaluate and manage occupational risks. A total of 30 potential hazards were identified, classified into five categories: physical, mechanical, chemical, biological, and ergonomic. The risk assessment indicated that 3.33% of the risks were low, 36.67% medium, 56.67% high, and 3.33% extreme. The recommended control measures included one elimination, two substitutions, eight engineering controls, twelve administrative controls, and five uses of personal protective equipment (PPE). The findings indicated a high proportion of hazards with significant risk levels, underscoring the urgent need for comprehensive risk mitigation. Effective implementation of the recommended control measures was expected to improve occupational safety and health at TPA Suwung. Strengthening OHS management systems and conducting regular monitoring were crucial to sustaining a safe and healthy work environment.